2022
DOI: 10.1002/ajs4.201
|View full text |Cite
|
Sign up to set email alerts
|

Fulfilling and desperately needed: Australian media representations of responses to homelessness

Abstract: Homelessness is a significant social issue that continues to confront Australian society, despite burgeoning public and policy responses to the issue. Existing scholarship demonstrates the important role the media can play in shaping such responses by framing homelessness – and the people who experience it – in particular ways. However, to date there has been limited focus on how the media represents social responses to homelessness, or how such representations might influence public perceptions of the appropr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…through homelessness) have indicated that consumer participation is one of the “key factors to promote positive [health] service experiences” (Luchenski et al, 2018, p. 273) and that even evidence‐based practice is insufficient without allowing “service users' insights to contribute to the development of treatments and support mechanisms” (Davies & Gray, 2017, p. 10). Furthermore, the absence of the voices of lived experience has potentially contributed to misrepresentations of homelessness service user needs and therefore to a trend of interventions that do not directly address homelessness (Simpson Reeves et al, 2022). However, as O'Keefe and David (2022) demonstrate, in their analysis of the marketisation of “consumer choice” principles in human services, potential benefits and good values can be lost when there is a lack of clarity as to how these are to be effectively implemented and measured.…”
Section: Introductionmentioning
confidence: 99%
“…through homelessness) have indicated that consumer participation is one of the “key factors to promote positive [health] service experiences” (Luchenski et al, 2018, p. 273) and that even evidence‐based practice is insufficient without allowing “service users' insights to contribute to the development of treatments and support mechanisms” (Davies & Gray, 2017, p. 10). Furthermore, the absence of the voices of lived experience has potentially contributed to misrepresentations of homelessness service user needs and therefore to a trend of interventions that do not directly address homelessness (Simpson Reeves et al, 2022). However, as O'Keefe and David (2022) demonstrate, in their analysis of the marketisation of “consumer choice” principles in human services, potential benefits and good values can be lost when there is a lack of clarity as to how these are to be effectively implemented and measured.…”
Section: Introductionmentioning
confidence: 99%